Q: skills for Success : Reading and Writing - Lynn, Sarah (Oxford University Press, 2011)
This book teaches reading and writing skills in 10 lessons. These unique forms of instruction reflect a critical-thinking approach to learning English and are suitable for English learners ready to prepare for other subjects.